Alexithymia and memory for facial emotions - Donges, Uta-Susan; Department of Psychosomatic Medicine, University of Leipzig (2014)
Alexithymia is a multi-faceted personality construct that encompasses, among other features, difficulties in identifying and describing emotions. Prior research suggests that alexithymia is associated with poor recognition memory for emotional words. This study addressed the question of whether memory for emotional faces varies as a function of alexithymia. The 20-Item Toronto Alexithymia Scale (TAS-20), and measures of depression, trait anxiety and intelligence were administered to 40 healthy women. During the encoding experiment angry, fearful, happy, and neutral faces were presented. After 30 minutes a recognition test was conducted. Partial correlation analysis revealed that the TAS-20 scale Difficulties describing feelings was inversely correlated with correct recognition of fearful and angry faces. Alexithymia appears to adversely affect memory functioning for negative emotional faces.